'A Word of Song': Reverberations of the Psalms in Christina Rossetti's Roundels. (27th September 2021) - Johnson, Stephanie L
Abstract: Christina Rossetti's Verses (1893) collects poetry published originally in her devotional prose works, and 57 of its 331 lyric poems are roundels. Structured helically, the roundels use refrains to accrue meaning through repetition with a difference. While Rossetti follows Swinburne's 11-line form, she uses the songs of the Word—the liturgical and wisdom psalms in particular—as the inspiration for her words of song. By recognising the antiphonal dialogue of the roundels modelled on the Psalms, we see more clearly how Rossetti's lyric poetry emphasises not introspection or a Romantic solipsism but rather an interchange with others that turns its participants toward God. The reverberations of the Psalms in her roundels make audible her commitment to a communal, lyric form that unites its dialogic participants in worship and in an inclusive eschatology; that overlays the temporal with the eternal; and that conveys the priestly act of proclaiming the Kingdom of God in the present.